A New Cation‐Ordered Structure Type with Multiple Thermal Redistributions in Co2InSbO6. Issue 27 (21st April 2022) - Ji, Kunlang; Solana‐Madruga, Elena; Patino, Midori Amano; Shimakawa, Yuichi; Attfield, J. Paul
Abstract: Cation ordering in solids is important for controlling physical properties and leads to ilmenite (FeTiO3 ) and LiNbO3 type derivatives of the corundum structure, with ferroelectricity resulting from breaking of inversion symmetry in the latter. However, a hypothetical third ABO3 derivative with R 32 symmetry has never been observed. Here we show that Co2 InSbO6 recovered from high pressure has a new, ordered‐ R 32 A2 BCO6 variant of the corundum structure. Co2 InSbO6 is also remarkable for showing two cation redistributions, to (Co0.5 In0.5 )2 CoSbO6 and then Co2 InSbO6 variants of the ordered‐LiNbO3 A2 BCO6 structure on heating. The cation distributions change magnetic properties as the final ordered‐LiNbO3 product has a sharp ferrimagnetic transition unlike the initial ordered‐ R 32 phase. Future syntheses of metastable corundum derivatives at pressure are likely to reveal other cation‐redistribution pathways, and may enable ABO3 materials with the R 32 structure to be discovered. Abstract : Corundum‐derived Co2 InSbO6 undergoes an unprecedented sequence of cation rearrangements on heating, from a previously unreported ordered‐ R 32 type distribution to two successive ordered‐LiNbO3 type arrangements.